2020
DOI: 10.1186/s12955-020-01388-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health related quality of life of patients with stroke in Sri Lankan context

Abstract: Background Stroke is a major global health concern which affects the health related quality of life (HRQOL). As the prevalence of stroke is increasing especially in lower-middle income countries, it is vital to identify the factors associated with the HRQOL of affected individuals. Available literature for post stroke HRQOL and the associated factors are mainly from high income countries. Therefore, we conducted this study to identify the factors associated with HRQOL of stroke survivors using a stroke specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Based on the present study, the mean cognitive problems had a significant relationship with the level of satisfaction with services and overall satisfaction (P=0.032 and P=0.026 respectively), which was consistent with Baumann's studies [17] and Kariyawasam [18]. According to Baumann's study, cognitive-functional problems, like memory problems and sensory problems, showed a significant and direct relationship with low levels of quality of life.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the present study, the mean cognitive problems had a significant relationship with the level of satisfaction with services and overall satisfaction (P=0.032 and P=0.026 respectively), which was consistent with Baumann's studies [17] and Kariyawasam [18]. According to Baumann's study, cognitive-functional problems, like memory problems and sensory problems, showed a significant and direct relationship with low levels of quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results, various quality of life domains were strongly related to dissatisfaction with the help received and coordination between services [17]. Based on the results of Kariyawasam's study, the quality of life of stroke patients had a significant relationship with the level of cognitive problems like speech problems [18].…”
Section: What This Article Addsmentioning
confidence: 99%
“…This was contradicted with results that were found in a study conducted by Butsing et al (2022), which revealed that the patients after an ischemic stroke showed a significantly higher overall QOL compared to patients after a hemorrhagic stroke. Moreover, Kariyawasam et al (2020) pointed out in their study that aims at identifying the factors associated with QOL of Notes: SS-QOL: stroke-specific quality of life, SD: standard deviation. Ã p-value is significant at < 0.05 stroke survivors in lower-middle-income countries; that the lowest degree of QOL was associated with patients who had a hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of high blood pressure and other risk factors on stroke survivors have been reported by previous studies. [36,37] The present study has some clinical significance. Beta-inflated-regression-at-one model percentages are better, allowing a more straightforward and intuitive transformation of discrete data usually generated among stroke survivors.…”
Section: Discussionmentioning
confidence: 58%